2016
DOI: 10.15632/jtam-pl.54.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical properties of epoxy by adding multi-wall carbon nanotube

Abstract: In this research, multi-walled carbon nanotubes (MWCNTs) are used as the reinforcement in an epoxy resin with weight percentages (0, 0.2, 0.4, 0.6, 0.8, 1) wt%, respectively, by using both direct (nonhomogeneous) and homogeneous dispersion mixing processes to prepare (epoxy/MWCNTs) nanocomposites. Tensile and drop weight impact tests are used to evaluate mechanical properties of the composites. Results show that homogeneous dispersion has a great effect on enhancing mechanical properties of multi-wall carbon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Fibrillation was hardly observed in AF/PAE/L4. This is attributed to the fact that the MWCNTs-COOH form a network structure on the fiber surface, and when the apply loading is over the elastic deformation stress, the MWCNTs-COOH transfer the stress . During the puncture test, this network structure acted as a protective layer to increase the fiber resistance to the impact load.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrillation was hardly observed in AF/PAE/L4. This is attributed to the fact that the MWCNTs-COOH form a network structure on the fiber surface, and when the apply loading is over the elastic deformation stress, the MWCNTs-COOH transfer the stress . During the puncture test, this network structure acted as a protective layer to increase the fiber resistance to the impact load.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the fact that the MWCNTs-COOH form a network structure on the fiber surface, and when the apply loading is over the elastic deformation stress, the MWCNTs-COOH transfer the stress. 37 During the puncture test, this network structure acted as a protective layer to increase the fiber resistance to the impact load. L-MWCNTs-COOH were interlaced with each other; thus, they were more conducive to uniformly dispersing and transferring stress.…”
Section: Resultsmentioning
confidence: 99%
“…It had been noted that the nanocomposites and the neat composites showed better performance than the Al plates, but lesser bumper shields (Khatiwada et al, 2013). Fadhil et al (2016) utilized weight percentages (0, 0.2, 0.4, 0.6, 0.8, 1) Wt.% of multi-walled carbon nanotubes (MWCNTs) to reinforce epoxy resin. Mechanical properties of the composites were assessed by tensile and drop-weight impact tests.…”
Section: Mmms 166mentioning
confidence: 99%
“…Mechanical properties of the composites were assessed by tensile and drop-weight impact tests. The results revealed that 0.2 Wt.% of MWCNTs improve tensile properties, whereas 0.6 Wt.% of MWCNTs improve impact characteristics (Fadhil et al, 2016). Ahmed (2016) used different designs of the impactor in drop-weight impact test (bullet, cone and hemispherical) and investigated this effect on the impact properties of epoxy composites reinforced with unidirectional glass, unidirectional carbon, woven glass and hybrid woven (glass þ carbon) fibers.…”
Section: Mmms 166mentioning
confidence: 99%
“…Tensile and drop weight impact test are used to evaluate the mechanical properties of the composites. Results shows that adding 0.2 wt.% of MWCNTs enhance and increase the tensile properties and Adding 0.6 wt.% of MWCNTs enhance the impact properties [3]. Impact characteristics of epoxy matrix composites have been studied by Payman S. A. et.…”
Section: Introductionmentioning
confidence: 99%